2019
DOI: 10.1016/j.pvr.2019.100172
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical study of safety and immunogenicity of combined rubella and human papillomavirus vaccines: Towards enhancing vaccination uptake rates in developing countries

Abstract: Rubella vaccine was not part of national immunization programs (NIP) in several countries in the Middle East and North Africa (MENA), South-East Asia (SEA), and South Africa regions until the year 2000. Therefore, immunization coverage of females older than 20 years old in these countries has been the focus of national campaigns for rubella elimination in developing countries. Vaccines against human papillomavirus (HPV) are not part of NIPs in developing countries. To enhance the advantages of rubella-directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the same study, only 27.9% of the participants knew about the HPV vaccine, and only 1.4% had been vaccinated. In another study, 520 nursing students working in a tertiary health institution in Ankara and a control group of 232 people were evaluated (7). This study, which was conducted among female health workers about HPV, showed that awareness knowledge/ awareness of HPV is high among female health workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, only 27.9% of the participants knew about the HPV vaccine, and only 1.4% had been vaccinated. In another study, 520 nursing students working in a tertiary health institution in Ankara and a control group of 232 people were evaluated (7). This study, which was conducted among female health workers about HPV, showed that awareness knowledge/ awareness of HPV is high among female health workers.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to cancers that develop in other parts of the body, cervical cancer and its precursor lesions are treatable in the early stages of the disease and can be detected early. The majority of women do not typically exhibit symptoms until the disease has progressed, making cervical cancer screenings essential (7). Awareness of the condition, screening methods, and preventive measures are all essential to the prevention and control of cervical cancer (8).…”
Section: Introductionmentioning
confidence: 99%